Enhancing Arabic communication proficiency in Malaysian among Malaysian students: barriers, pedagogical strategies, and environmental influences - Abdul Ghani, Mohammad Taufiq; Mohamed Shalikin, Nor Hadisah; Ramli, Saipolbarin; Mohd Zakaria, Zarima; Wan Daud, Wan Ab Aziz; Amiruddin, Ahmad Zaki; Ahmad, Muhammad Anwar (Learning Gate, 2025)
The purpose of this study is to explore the factors contributing to low proficiency in Arabic communication among students in government-assisted religious schools (SABK) in Malaysia, despite a structured curriculum that emphasizes communicative competence. Using a qualitative research design, data were collected through semi-structured interviews with 20 experienced Arabic language teachers. The study identifies several key barriers, including low student motivation, negative attitudes, fear, and lack of self-confidence, which significantly reduce students’ willingness to communicate in Arabic. Pedagogical challenges such as limited integration of Arabic in daily classroom interactions, teacher-centered instruction, inadequate use of interactive teaching tools, and insufficient time for speaking practice were also noted. Environmental factors—such as minimal parental involvement, peer ridicule, absence of extracurricular reinforcement, and lack of immersive Arabic-speaking environments—further hinder language development. The findings suggest that overcoming these challenges requires a holistic approach involving all stakeholders. The study concludes that enhanced parental engagement, student-centered and technology-based teaching methods, and school-wide Arabic initiatives are essential. Practical implications highlight the need for strategic interventions, including gamification, experiential learning, and mobile language applications, to support the development of Arabic communication skills in SABK settings.